Odpowiedzi

2010-03-01T20:16:23+01:00
2a+(3a-7)=2a+3a-7=5a-7
x-(2x-3)=x-2x+3=-x+3
3x-(y-2x)=3x-y+2x=5x-y
-(3a+6)-4=-3a-6-4=-3a-10
-(2x-1)-(3x+1)=-2x+1-3x-1=-5x
(4a-7b)-(2a+3b)=4a-7b-2a-3b=2a-10b
(2p-r)+(2r-p)=2p-r+2r-p=-3p+r
(x+y)+(x-2)+(2-y)=x+y+x-2+2-y=2x
7 3 7
2010-03-01T20:18:16+01:00
A) 2a+(3a-7)=2a+3a-7=5a-7

b)x-(2x-3)=x-2x+3=-x+3

c)3x-(y-2x)=3x-y+2x=5x-y

d)-(3a+6)-4=-3a-6-4=-3a-10

e)-(2x-1)-(3x+1)=-2a+1-3x-1=-2a-3x

f)(4a-7b)-(2a+3b)=4a-7b-2a-3b=2a-10b

g)(2p-r)+(2r-p)=2p-r+2r-p=p+r

h)(x+y)+(x-2)+(2-y)=x+y+x-2+2-y=2x-2

mam nadzieje ze omoglam i licze na naj;)
9 4 9